Entropy of Mixing of Cadmium-based Liquid Alloys - Chakrabarti, S. K.; Jha, B. K.; Jha, I. S. (Journal of Nepal Chemical Society, 2010)
Cadmium is a highly reactive metal. At the time of formation of binary alloys in liquid phase it often forms complexes. In the present work we have considered two such complex forming binary liquid alloys of cadmium e.g. Cd-Na and Cd-Mg. The former alloy shows anomaly in its thermodynamic properties of mixing. On the other hand, the alloying behavior of the latter one is symmetric around the equi-atomic composition. We have computed their entropy of mixing (SM) for different concentrations of the ingredients by using the quasi-lattice chemical model. The results explain the observed anomaly as well as symmetry in SM of the present alloys. Keywords: Binary liquid alloys of cadmium; Quasi-lattice chemical model; Entropy of mixing DOI: 10.3126/jncs.v26i0.3629 Journal of Nepal Chemical Society Vol. 26, 2010 Page:40-45